1980
DOI: 10.1172/jci109955
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-directed inhibition of chemotactic factor-induced neutrophil hyperactivity by pyrazolon derivatives. Definition of a chemotactic peptide antagonist.

Abstract: A B S T R A C T The two pyrazolon derivatives, phenylbutazone and sulfinpyrazone, selectively inhibit chemotactic peptide-induced effects on neutrophils. As they antagonize the induction of acute neutropenia in vivo and of cellular hyperadhesiveness, lysosomal enzyme release, hexose monophosphate shunt activity, and superoxide production in vitro, these effects occur with a specificity not shared with other prostaglandin biosynthesis inhibitors. Inhibition by these drugs resembles the competitive type ofantago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…PB treatment was administered in the present study at doses that others have shown to completely prevent the neutropenia induced in rabbits by iv injection of the formylpeptide formyl-methionylleucyl-phenylalanine [12]. Although a different efficacy of this drug in the rat can not be excluded, ratio (table 1).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…PB treatment was administered in the present study at doses that others have shown to completely prevent the neutropenia induced in rabbits by iv injection of the formylpeptide formyl-methionylleucyl-phenylalanine [12]. Although a different efficacy of this drug in the rat can not be excluded, ratio (table 1).…”
Section: Resultsmentioning
confidence: 90%
“…Hypocomplementemia was checked by measuring levels of total serum hemolytic complement (CH so ) and immunoreactive C3 and the capacity of the serum to generate in vitro neutrophil migration upon zymosan activation. Second, rats were treated with phenylbutazone (PB), a competitive inhibitor of chemotactic formylpeptides for neutrophil receptors [11][12][13], in doses that prevented formylpeptide-induced neutropenia in rabbits [12]. Some of the animals were killed during the acute phase of pyelonephritis, and the neutrophil infiltration of their kidney parenchyma was determined by measuring the myeloperoxidase (MPO) activity, an enzymatic marker for neutrophil infiltration [1].…”
mentioning
confidence: 99%
“…They found that two other anti-inflamrnatory drugs, phenylbutazone and sulfinpyrazone possess in vivo, as well as in vitro, potent antagonistic properties against FMLP-induced PMN alteration in rabbits, and in vitro in human. They found also that both drugs were inhibitors of the binding of [14]. However, this result is not surprising since 100% autologous heat-inactivated plasma was used in the radioligand binding assay [14].…”
Section: Discussionmentioning
confidence: 99%
“…They found also that both drugs were inhibitors of the binding of [14]. However, this result is not surprising since 100% autologous heat-inactivated plasma was used in the radioligand binding assay [14].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for this phenomenon are presently unknown. Since endotoxin and fMLP possess similar granulocyte activating potencies [3], we suggest that endotoxin-induced endothelial damage may play an essential role: if fMLP-activated, hyperadhesive [4] granulocytes encounter endothelial cells that have been injured by endotoxin (an injury that does not occur with fMLP alone), the result is a deleterious sequence of events (e.g., persistent neutropenia; see table). In contrast, if granulocytes activated by either endotoxin or fMLP encounter native, undamaged endothelium, subsequent alterations remain limited.…”
Section: Streptococcus Faecalismentioning
confidence: 99%